2006
DOI: 10.1145/1151659.1159935
|View full text |Cite
|
Sign up to set email alerts
|

Network monitors and contracting systems

Abstract: Today's Internet industry suffers from several well-known pathologies, but none is as destructive in the long term as its resistance to evolution. Rather than introducing new services, ISPs are presently moving towards greater commoditization. It is apparent that the network's primitive system of contracts does not align incentives properly. In this study, we identify the network's lack of accountability as a fundamental obstacle to correcting this problem: Employing an economic model, we argue that optimal ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Accountability has been suggested as an avenue through which to accomplish practical security [9], to nurture healthy competition and innovative work in the Internet [10][11], and even has been considered to be a common objective of design for reliable networks [12]. However, the issue of whether accountability can be realized in an efficient and practical way still exists [13].…”
Section: Introductionmentioning
confidence: 99%
“…Accountability has been suggested as an avenue through which to accomplish practical security [9], to nurture healthy competition and innovative work in the Internet [10][11], and even has been considered to be a common objective of design for reliable networks [12]. However, the issue of whether accountability can be realized in an efficient and practical way still exists [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [28] advocated the use of the Shapley profit-sharing mechanism for multi-lateral ISP settlements and studied bilateral implementations [29]. Laskowski [25] identified that the network's lack of accountability is an obstacle to implement desirable contracting systems for the Internet. Because accounting of traffic towards the end-users is feasible for access ISPs, our subsidization mechanism can be regarded as a contracting system between the CPs and access ISPs, even through they might not be directly connected to each other.…”
Section: Bilateral Settlements For Valued Servicesmentioning
confidence: 99%
“…This line of works mostly focuses on handling the free-riding behaviors in P2P networks [14]. Other recent works that worth noting are [15] [16]. In [15], economic models were introduced to analyze the dynamic interactions between an incumbent and an entrant.…”
Section: B the Effect Of Hit Ratiomentioning
confidence: 99%
“…In [15], economic models were introduced to analyze the dynamic interactions between an incumbent and an entrant. The work in [16] studied the issue that is related to accountability, contracts, competition, and innovation in the specific context of network monitoring and contracting system.…”
Section: B the Effect Of Hit Ratiomentioning
confidence: 99%